The four spaces: a model for the physical organization of the library - Gallo-León, José-Pablo (Anuario ThinkEPI, 2018)
The irruption of technology has caused deep changes in library design. Digital collections free up space previously occupied by paper, while new services and commons are created. Librarians and architects do not have enough benchmarks or standards to guide the redesign of spaces caused by these changes. The Danish concept of the "four spaces", introduced in the Model Programme for Public Libraries, could be useful for this purpose in public libraries.
Keywords: Four spaces; Library buildings; Future of libraries; Public libraries.